Prosecuting Cybercrimes the Law, Procedure and Practical Realities - Mirembe Joan Kafeero (Uganda Christian University, 2024)
Understanding the origins, evolution, and current landscape of cybercrime is crucial for developing effective strategies to combat and mitigate its impact. This research aims to provide a comprehensive analysis of the background of cybercrime in Uganda, delving into its historical roots, theoretical, conceptual and contextual background driving its proliferation.